CUSTOMERS’ PURCHASE INTENTION TOWARDS ONLINE SHOPPING OF ORGANIC PRODUCTS IN SOUTHERN DISTRICTS OF TAMIL NADU - S. V. Divya; P. Amutha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The recent buzz of today’s world is associated with the term”Organic”. Organic products have become the most sought after due to the increase in the day to day ailments. After COVID-19, there has been a drastic change in the consumer preference towards organic products. Be it foods, beverages, milk and even textiles, the organic products sector has been growing tremendously over the past few years. Increase in the global demand, increasing customer awareness and the extensive government support to boost the sector have played a significant role in creating a strong impetus to this sector. Moreover,With varied options available, people have opted online shopping for purchasing the organic products. Online platforms offer numerous organic products, sourced from various states delivered at the doorstep, customers have started preferring online platforms over conventional method of purchasing. Online platforms also offer wide range of discounts and offers which attract the customer to purchase it online. Along with these benefits, online shopping of organic products offer innumerous advantages like convenience, price comparison, cash on delivery,etc. The respondents were contacted on the basis of purposive sampling. A sample of 640 respondents were selected from the study area.Statistical tools like simple percentage, ranking technique and weighted average score were used to analyse the collected data.